Smart and sustainable intelligent systems - Gupta, Namita; Chatterjee, Prasenjit, 1982-; Choudhury, Tanupriya (John Wiley & Sons, Inc., 2021)
"The world is experiencing an unprecedented period of change and growth through all the electronic and technological developments and everyone on the planet has been impacted. What was once "science fiction', today it is a reality. This book explores the world of many of once unthinkable advancements by explaining current technologies in great detail. Each chapter focuses on a different aspect--Machine Vision, Pattern Analysis and Image Processing--Advanced Trends in Computational Intelligence and Data Analytics--Futuristic Communication Technologies--Disruptive Technologies for Future Sustainability. The chapters include the list of topics that spans all the areas of smart intelligent systems and computing such as: Data Mining with Soft Computing, Evolutionary Computing, Quantum Computing, Expert Systems, Next Generation Communication, Blockchain and Trust Management, Intelligent Biometrics, Multi-Valued Logical Systems, Cloud Computing and security etc. An extensive list of bibliographic references at the end of each chapter guides the reader to probe further into application area of interest to him/her"-- Provided by publisher.
Keywords: Expert systems (Computer science); Artificial intelligence -- Industrial applications.; Machine learning.; Computer vision.; Speech processing systems.; elektronické knihy; electronic books